2014
DOI: 10.1105/tpc.113.119255
|View full text |Cite
|
Sign up to set email alerts
|

The Rice TAL Effector–Dependent Resistance Protein XA10 Triggers Cell Death and Calcium Depletion in the Endoplasmic Reticulum

Abstract: The recognition between disease resistance (R) genes in plants and their cognate avirulence (Avr) genes in pathogens can produce a hypersensitive response of localized programmed cell death. However, our knowledge of the early signaling events of the R gene-mediated hypersensitive response in plants remains limited. Here, we report the cloning and characterization of Xa10, a transcription activator-like (TAL) effector-dependent R gene for resistance to bacterial blight in rice (Oryza sativa). Xa10 contains a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
256
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(259 citation statements)
references
References 80 publications
(118 reference statements)
2
256
0
1
Order By: Relevance
“…We have analyzed the EBE prediction scores of all the known executor R genes and found that the score for EBE AvrXa23 is more than twice the scores for EBE AvrXa10 , EBE AvrXa27 , EBE AvrBs3 , and EBE AvrBs4 (Supplemental Table 2), indicating that the RVDs of AvrXa23 poorly match to the EBE AvrXa23 sequence. Consistently with the scores, the binding affinities of the cognate TALEs to EBE AvrXa10 , EBE AvrXa27 , EBE AvrBs3 , and EBE AvrBs4 are much stronger (Rö mer et al, 2007;Strauß et al, 2012;Tian et al, 2014) than that between AvrXa23 and EBE AvrXa23 (Figure 6B and 6C).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…We have analyzed the EBE prediction scores of all the known executor R genes and found that the score for EBE AvrXa23 is more than twice the scores for EBE AvrXa10 , EBE AvrXa27 , EBE AvrBs3 , and EBE AvrBs4 (Supplemental Table 2), indicating that the RVDs of AvrXa23 poorly match to the EBE AvrXa23 sequence. Consistently with the scores, the binding affinities of the cognate TALEs to EBE AvrXa10 , EBE AvrXa27 , EBE AvrBs3 , and EBE AvrBs4 are much stronger (Rö mer et al, 2007;Strauß et al, 2012;Tian et al, 2014) than that between AvrXa23 and EBE AvrXa23 (Figure 6B and 6C).…”
Section: Discussionsupporting
confidence: 75%
“…These data indicate that XA23 is a homolog of XA10; plant genomes have convergent executor R genes with different EBEs. It has been shown that there are five putative paralogs of XA10 in cultivated and wild rice species but they have not been assigned a function (Tian et al, 2014). One of the paralogs in Nipponbare (National Center for Biotechnology Information accession number ABA94457), which is annotated as a 163-aa protein, is in fact encoded by a predicted gene that is allelic to Xa23 (ORF113).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations